Wikalah iBT: How Is An Internet-Based Arabic Language Proficiency Test Instrument Developed? - Syihabuddin, Syihabuddin; Abdurrahman, Maman; Akmalia, Frida; Abdussalam, Aam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study discusses the development of 140 items of Arabic language proficiency test which covers listening, reading, and grammar mastery. These items were empirically analyzed, tried out, and revised. Results of this development would then be made a basis to design an application that can evaluate internet-based Arabic language proficiency (Internet-based Taqwim Kafa`ah Maharah Lughah Arabiyah) abbreviated as Wikalah iBT. To achieve this goal, a developmental research method was employed, namely the development of instruments starting from the needs analysis for tests, the making of instruments, validity and reliability testing, the design of iBT program, and the trial of the Wikalah iBT application. Results of the study show that (a) several test items still had morphological, morphosyntactic, and technical errors, (b) 81 test items were valid, (c) average reliability level was 0.67, (d) this test was in the medium and easy categories (63.57), and (e) the iBT application design was used successfully and ran smoothly. Based on the conclusions, it is recommended to add the test item package, improve the quality of the questions, and evaluate the iBT application. We believe that these findings provide initial support forÂ making an overview to those preparing for theÂ iBT test or other similar tests ofÂ language proficiency. Study outcomes also inform the extent to which the use of technology can evaluate language proficiency